PENGARUH HARGA, KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PUPUK DOLOMIT PT GALATTA LESTARINDO. - Manullang, Januardin; Samosir, Hottua (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
PT Galatta Lestarindo is a company engaged in the Dolomite fertilizer distributor. This Dolomite fertilizer is often used by farmers in planting their crops. The purpose of this study was to examine and analyze the effect of price and product quality on customer satisfaction PT Galatta Lestarindo dolomite fertilizer partially and simultaneously. This research method is to use quantitative methods, the data analysis model of this study uses multiple regression analysis with analytical tools using SPSS. The results of this study are that the adjusted R Square coefficient is 0.310. Partially And simultaneously price and product quality have a positive and significant effect on customer satisfaction. Keywords: Price, Product Quality, Customer Satisfaction